The farm novel in North America genre and nation in the United States, English Canada, and French Canada, 1845-1945 - Freitag, Florian (Boydell & Brewer, 2013)
From John Steinbeck's 'The Grapes of Wrath' and Martha Ostenso's 'Wild Geese' to Louis Hémon's 'Maria Chapdelaine', some of the most famous works of American, English-Canadian, and French-Canadian literature belong to the genre of the farm novel. In this volume, Florian Freitag provides the first history of the genre in North America from its beginnings in the middle of the 19th century to its apogee in French Canada around the middle of the 20th. Through surveys and selected detailed analyses of a large number of farm novels written in French and English, Freitag examines how North American farm novels draw on the history of farming in 19th-century North America as well as on the national self-conceptions of the United States, English Canada, and French Canada, portraying farmers as national icons and the farm as a symbolic space of the American, English-Canadian, and French-Canadian nations. Turning away from traditional readings of farm novels within the frameworks of regionalism and pastoralism, Freitag takes a comparative North American look at a genre that helped to spatialize North American national dreams. Florian Freitag is Assistant Professor of American Studies at the University of Mainz, Germany